2021
DOI: 10.1038/s41525-021-00223-7
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic heterogeneity of the consensus molecular subtypes of colorectal cancer

Abstract: Gene expression-based subtypes of colorectal cancer have clinical relevance, but the representativeness of primary tumors and the consensus molecular subtypes (CMS) for metastatic cancers is not well known. We investigated the metastatic heterogeneity of CMS. The best approach to subtype translation was delineated by comparisons of transcriptomic profiles from 317 primary tumors and 295 liver metastases, including multi-metastatic samples from 45 patients and 14 primary-metastasis sets. Associations were valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…By adapting CMS classification to liver metastases and developing a new version of the R package CMScaller [ 38 ] (v2.0.1), we have shown that CMS has limited discriminatory power in CRLM [ 34 ]. Most metastatic lesions were classified into one of only two subtypes, based on epithelial-mesenchymal characteristics (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By adapting CMS classification to liver metastases and developing a new version of the R package CMScaller [ 38 ] (v2.0.1), we have shown that CMS has limited discriminatory power in CRLM [ 34 ]. Most metastatic lesions were classified into one of only two subtypes, based on epithelial-mesenchymal characteristics (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 . LMS showed only a moderate level of classification concordance with CMS, despite comparison with CMS classes obtained from a tailored classification of resected CRLM tissue samples [ 34 ]. LMS provided stronger biological and prognostic discriminatory power than CMS in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another layer of complexity could be represented by the presence of intrapatient tumor heterogeneity. 77 In this regard, an analysis of the transcriptomic profiles from 317 primary tumors and 295 liver metastases indicated that metastases were classified more frequently as CMS2 or CMS4 and less frequently as CMS1 or CMS3 compared with primary tumors. This heterogeneity may be a consequence of the complex tumor biology and of the interaction between cancer cells and the microenvironment.…”
Section: Consensus Molecular Subtype Classification Of Colorectal Cancermentioning
confidence: 96%
“…Of note, intratumor heterogeneity was correlated with reduced disease‐free survival and with worse OS. Another layer of complexity could be represented by the presence of intrapatient tumor heterogeneity 77 . In this regard, an analysis of the transcriptomic profiles from 317 primary tumors and 295 liver metastases indicated that metastases were classified more frequently as CMS2 or CMS4 and less frequently as CMS1 or CMS3 compared with primary tumors.…”
Section: Consensus Molecular Subtype Classification Of Colorectal Cancermentioning
confidence: 99%